Merits and challenges of iPSC-derived organoids for clinical applications - Xu, Ziran; Yang, Jiaxu; Xin, Xianyi; Liu, Chengrun; Li, Lisha; Mei, Xianglin; Li, Meiying (Frontiers in Cell and Developmental Biology, 2023)
Induced pluripotent stem cells (iPSCs) have entered an unprecedented state of development since they were first generated. They have played a critical role in disease modeling, drug discovery, and cell replacement therapy, and have contributed to the evolution of disciplines such as cell biology, pathophysiology of diseases, and regenerative medicine.. Organoids, the stem cell-derived 3D culture systems that mimic the structure and function of organs in vitro, have been widely used in developmental research, disease modeling, and drug screening. Recent advances in combining iPSCs with 3D organoids are facilitating further applications of iPSCs in disease research. Organoids derived from embryonic stem cells, iPSCs, and multi-tissue stem/progenitor cells can replicate the processes of developmental differentiation, homeostatic self-renewal, and regeneration due to tissue damage, offering the potential to unravel the regulatory mechanisms of development and regeneration, and elucidate the pathophysiological processes involved in disease mechanisms. Herein, we have summarized the latest research on the production scheme of organ-specific iPSC-derived organoids, the contribution of these organoids in the treatment of various organ-related diseases, in particular, its contribution to COVID-19 treatment, and have discussed the unresolved challenges and shortcomings of these models.